2009
DOI: 10.1111/j.1464-5491.2008.02658.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated plasma prostaglandins and acetylated histone in monocytes in Type 1 diabetes patients

Abstract: Results support increased inflammatory activity in Type 1 diabetes that involves COX-2 and increased prostaglandin production, which may predispose patients to cardiovascular events. The observation of elevated histone acetylation only in complication-free diabetic subjects suggests that this may be a protective mechanism. This merits further investigation as histone hyperacetylation has been associated with reduced expression of factors involved in vascular injury and remodelling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 20 publications
1
27
0
Order By: Relevance
“…Results from related in vivo studies confirmed that the increased histone acetylation can lead to inflammatory gene transcription under diabetic conditions [40]. Moreover, data from a clinical trial suggested that elevated acetylated histone levels play an important role in both vascular injury and remodeling in Type 1 diabetes [41]. Similar to these collective findings, our study of the STZ-induced diabetes mouse model showed that the diabetic condition was associated with significant increases in total HAT activity and H3K9/14Ac level.…”
Section: Discussionmentioning
confidence: 98%
“…Results from related in vivo studies confirmed that the increased histone acetylation can lead to inflammatory gene transcription under diabetic conditions [40]. Moreover, data from a clinical trial suggested that elevated acetylated histone levels play an important role in both vascular injury and remodeling in Type 1 diabetes [41]. Similar to these collective findings, our study of the STZ-induced diabetes mouse model showed that the diabetic condition was associated with significant increases in total HAT activity and H3K9/14Ac level.…”
Section: Discussionmentioning
confidence: 98%
“…Acetylated histone H4 levels in the circulating monocytes were significantly elevated in complication-free diabetic patients, but not in patients with complications, suggesting that protein acetylation in the monocytes may be a protective mechanism. 28 …”
Section: Discussionmentioning
confidence: 99%
“…Elevated PGs have been observed in type 1 and type 2 diabetes (3,4). Epidemiological studies have indicated that the use of nonselective nonsteroidal anti-inflammatory drugs (NSAIDs), including acetylsalicylic acid (ASA), is associated with a significant reduction in the risk of diabetes in healthy populations (5).…”
mentioning
confidence: 99%